Design for a new Europe - Gillingham, John, 1943- (Cambridge University Press, 2006)
This penetrating, fiercely-argued, witty book subjects today's dysfunctional European Union to critical scrutiny and demonstrates how Europe's great experiment in political and economic union can succeed only if the wave of liberal reform now under way in the historically downtrodden east is allowed to sweep the prosperous and complacent west.